Structure of a BCOR corepressor peptide in complex with the BCL6 BTB domain dimer - Ghetu, Alexandru F. (2008)
The transcriptional corepressors BCOR, SMRT and NCoR are known to bind competitively to the BCL6 BTB domain despite the fact that BCOR has no detectible sequence similarity to the other two corepressors. We have identified a previously uncharacterized 17 residue motif from BCOR that binds directly to the BCL6 BTB domain and determined the crystal structure of the complex to a resolution of 2.6 Å. Remarkably, the BCOR BCL6 Binding Domain (BCOR(BBD)) peptide binds in the same BCL6 binding site as the SMRT(BBD) peptide despite the lack of any significant sequence similarity between the two peptides. Mutations of critical BCOR(BBD) residues cause the disruption of the BCL6 corepression activities of BCOR, and a BCOR(BBD) peptide blocks BCL6-mediated transcriptional repression and kills lymphoma cells.